How to Play With Maps - Thorn, Ross (My University, 2018)
The research reported here responds to the growing calls in cartography to integrate elements of play and games into mapping products and process. Specifically, I investigated video game maps as a case study for enriching traditional cartographic principles with tenets of play. My research examined both the product and process of playful map design through the following questions: 1: How do video game maps exhibit interactivity, immersiveness, incompleteness, and inclusiveness of playful maps through traditional cartographic frameworks? and 2: How do video game maps utilize elements of interaction and representation as cartographic tools for play? Overall, the sampled video games provided an elucidating perspective on how playful maps conform to and diverge from traditional cartography. This researched highlighted opportunities where video game designers could improve their maps to enforce interactivity, immersiveness, incompleteness, and inclusiveness in their games according to cartographic principles, as well as where cartographers could investigate how the characteristics of playful maps might affect the way they think about interaction and representation. In the end, the relationship between games and space is strong and further examination into the overlap of the two could continue to improve each discipline. However, the implications of gameful design go well beyond cartography and hold potential to improve several industries and fields of study.
Includes Figures, Tables, Maps, Appendices and Bibliography.
Keywords: Maps; Playful Maps; Video games